Truth is a woman - Han, Agata (Acta Universitatis Lodziensis. Folia Iuridica, 2014)
The feminist critics of western epistemology reveal political implications of a conception of truth. As a consequence of this a legal process is also in a broad sense inflicted by politics. The feminist jurisprudence claims that the modern law is founded on patriarchal values and interests and neglects voices of social groups which are located on the edge of the society.